My brother, my land : a story from Palestine - Hermez, Sami, 1977-; Sawalha, Sireen, 1966- (Stanford, California : Redwood Press, 2024)
"In 1967, Sireen Sawalha's mother, with her young children, walked back to Palestine against the traffic of exile. My Brother, My Land is the story of Sireen's family in the decades that followed and their lives in the Palestinian village of Kufr Ra'i. From Sireen's early life growing up in the shadow of the '67 War and her family's work as farmers caring for their land, to the involvement of her brother Iyad in armed resistance in the First and Second Intifada, Sami Hermez, with Sireen Sawalha, crafts a rich story of intertwining voices, mixing genres of oral history, memoir, and creative nonfiction. Through the lives of the Sawalha family, and the story of Iyad's involvement in the Palestinian Islamic Jihad, Hermez confronts readers with the politics and complexities of armed resistance and the ethical tensions and contradictions that arise, as well as with the dispossession and suffocation of people living under occupation and their ordinary lives in such times. Whether this story leaves readers discomforted, angry, or empowered, they will certainly emerge with a deeper understanding of the Palestinian predicament"--
"Mother is going to give birth" -- "Don't leave me here" -- A promise and a pledge -- "Hold onto me" -- Return.
Includes bibliographical references.
Keywords: Sawalha, Sireen, -- 1966- -- Family; Palestinian Arabs -- West Bank -- Biography; Arab-Israeli conflict -- Personal narratives, Palestinian; Arab-Israeli conflict -- Occupied territories -- History; Biographies